2020
DOI: 10.1002/cbdv.202000561
|View full text |Cite
|
Sign up to set email alerts
|

Pili Tree (Canarium ovatum) Resin's Antibacterial Essential Oil and Hydrosol as Rich Sources of (S)‐Phellandrenes Derivatives

Abstract: Five batches of resin from the Pili tree (Canarium ovatum Engl.) were distilled, and their essential oils and hydrosols were analyzed by gas chromatography. The oils, obtained in yields of 13.4-19.7 % v/m, featured αphellandrene in high proportions (50-65 %), alongside limonene, β-phellandrene and para-cymene. Chiral GC analysis confirmed that both phellandrenes were in fact > 95 % (S)-(+) enantiomers, while the other monoterpenes featured less pronounced enantiomeric excesses. The hydrosols were rich in α-phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The results showed that the optimal antibacterial effect against S. aureus , E. coli and B. subtilis was due to the rosemary‐magnolia EOs, indicating that the combination gained a buff. The high correlation of α‐Phellandrene, Eucalyptol, Terpinolene and α‐Terpineol with the inhibition effect was also demonstrated in previous findings [49–53] . Using the rule of variation between constituent difference and biological activity, the EO compounds could be applied in the targeted inhibition of different kinds of strains.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The results showed that the optimal antibacterial effect against S. aureus , E. coli and B. subtilis was due to the rosemary‐magnolia EOs, indicating that the combination gained a buff. The high correlation of α‐Phellandrene, Eucalyptol, Terpinolene and α‐Terpineol with the inhibition effect was also demonstrated in previous findings [49–53] . Using the rule of variation between constituent difference and biological activity, the EO compounds could be applied in the targeted inhibition of different kinds of strains.…”
Section: Discussionsupporting
confidence: 56%
“…The high correlation of α-Phellandrene, Eucalyptol, Terpinolene and α-Terpineol with the inhibition effect was also demonstrated in previous findings. [49][50][51][52][53] Using the rule of variation between constituent difference and biological activity, the EO compounds could be applied in the targeted inhibition of different kinds of strains. addition, according to the antioxidant effect and gray correlation analysis, the content of rosemary EO in the compounded EOs was positively correlated with the antioxidant effect, and its good antioxidant effect was attributed to the high content of β-Pinene.…”
Section: Discussionmentioning
confidence: 99%
“…This group, headed by Boucher [ 81 ], also studied its activity against E. coli with a MIC 50 of 468.0 µg/mL. Mercier et al [ 21 ] focused, likewise, on these two specific and common pathogens, finding that the EO from Canarium ovatum , with 64.9% of alpha-phellandrene, had an MIC 90 of 180.0 and 310.0 µg/mL against E. coli and S. aureus , respectively. Further proof of the antimicrobial potential of this molecule was given by Dalli et al [ 82 ], testing Nigella sativa seed EO against different bacterial strains, and obtaining promising results against Acinetobacter baumannii .…”
Section: Resultsmentioning
confidence: 99%